Camp nine : a novel - Schiffer, Vivienne, 1959- (Book collections on Project MUSE., 2011)
Vivienne Schiffer is a novelist and filmmaker who grew up in Desha County, Arkansas, and lives in Houston, Texas. She is currently at work on various film projects, including Relocation, Arkansas, a documentary about the Arkansas camps, as well as a second novel.